2021
DOI: 10.1038/s41598-021-03210-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following long versus short cephalomedullary devices for fixation of extracapsular hip fractures: a systematic review and meta-analysis

Abstract: Although both long and short cephalomedullary devices (CMDs) are used in the treatment of extracapsular hip fractures, the advantages of either option are subject to debate. This study aims to evaluate the differences in clinical outcomes with long versus short CMDs for extracapsular hip fractures. Studies included must have included subjects with at least 1 year of follow-up and reported on at least one of the following outcomes: rate of reoperation; rate of peri-implant fracture; operating time; blood loss; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Between January 2000 and March 2023, of 659 articles screened, 22 met the inclusion criteria and formed the basis of this study. 7,16–36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Between January 2000 and March 2023, of 659 articles screened, 22 met the inclusion criteria and formed the basis of this study. 7,16–36…”
Section: Resultsmentioning
confidence: 99%
“…19,27,31,36 However, the long nails were associated with increased estimated blood loss (EBL) and longer operative time. 17,19,27,31,[34][35][36] Interestingly, one study demonstrated a weighted mean difference of 17.57 minutes in operative time in favor of the short CMN group (P , 0.05) and estimated 60 mL reduced EBL. 17 No difference between the 2 nail groups was reported for mean length of hospitalization, 31,34,36 1 year mortality rate, 17,27,31,34,36 nonmechanical complication rate, 1,27,31,36 and patient-reported outcome measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is conflicting evidence regarding the incidence of periprosthetic fractures with each device. Several studies from the 1990s [ 8 , 9 ] and a recent meta-analysis have shown a higher incidence of periprosthetic fractures in the short PFN cohort [ 10 ]. Other studies have shown a lower reoperation rate with short PFNs [ 11 , 12 ], and no statistically significant differences have been quoted in the rates of periprosthetic fractures in systematic reviews [ 12 ].…”
Section: Introductionmentioning
confidence: 99%